'My Lifestyle Kind of Locks Me into Supermarket Shopping': Narratives of Reflexivity and Routines from Supermarket Shoppers in Australia. Issue 3 (3rd May 2020) - O'Kane, Gabrielle M.; Pamphilon, Barbara
ABSTRACT: This paper focusses on the supermarket shopper, who makes both reflexive and routine decisions while undertaking his or her regular shopping and cooking practices. The research used narrative inquiry methodology and convenience sampling to gather stories about a group of supermarket shoppers' perceptions of, and engagement with their chosen food retail environment and their attitudes towards making more sustainable food choices. The analysis drew on theories of practice and a food choice model showing that this group of shoppers were aware of the challenges of the modern food system and held ideals about purchasing Australian-grown, ethically produced food, eating seasonally and devoting more time to shopping and cooking, but the intangible resource of time dominated their dynamic value negotiations.